ANALISIS KANDUNGAN KLORIN PADA AIR TEH CELUP BERDASARKAN SUHU DAN WAKTU PENCELUPAN TAHUN 2013 - Saurma Erni Selvita Silaban; Irnawati Marsaulina; Indra Chahaya S (Lingkungan dan Kesehatan Kerja, 2014)
ABSTRACT Tea is the most consumed beverage either cold or hot. One kind of them is bag tea products. Tea bag is wrapped in smooth porous paper and heat resistant. In general, the paper uses chlorine as a bleach, it is the reason for necessary to study the chlorine content in water of tea bag. The purpose of this study was to determine the chlorine content in water of tea bag based on temperature and time. The kind of this study is descriptive survey. The object of study is the water of tea bag mixing in drinking water then examined in laboratorium of Balai Teknik Kesehatan Lingkungan Dan Pemberantasan Penyakit Menular Kelas I Medan by using spectrophotometric method. Based on the findings, there is the chlorine content of tea bag water at 400-1000C with immersion time respectively 1 minutes, 3 minutes and 5 minutes. The survey results revealed that the chlorine content increased by the increasing of temperature and time. The chlorine content is 1.35 mg/250 ml in temperature of 900c with 3 minutes immersion and chlorine content 0.2817 mg/250 ml in temperature of 800c with 3 minutes. Hence, it is concluded that the increasing of temperature and time will increase the chlorine in the tea bag water. It can be harmful health both in short and long term. According to Permenkes RI No. 492/Menkes/Per/IV/2010 that chlorine levels in drinking water is 1.25 mg/250 ml. It is suggested for frequent consumption of tea using brewed tea. Keywords : Chlorine, tea bags, temperature, time, spectrophotometry